EFFECT OF Artemisia vulgaris L. AQUEOUS EXTRACT ON SOME GERMINATION PROPERTIES AND SEEDLING GROWTH OF LINSEED : EFFECT OF Artemisia vulgaris L. AQUEOUS EXTRACT ON SOME GERMINATION PROPERTIES AND SEEDLING GROWTH OF LINSEED (Iraqi Journal of Market Research and Consumer Protection, 2022)
ABSTRACT            A laboratory experiment was carried out during winter season of 2021 in the Seed Technology Laboratory- College of Agricultural Engineering Sciences/ University of Baghdad, to find out the allopathic effects of aerobic and terrestrial aqueous extracts of Artemisia vulgaris L. on the seed germination and seedling growth of linseed. A factorial experiment according to a completely randomized design (CRD)at three replicates was used; the first factor in clouded type of aqueous extract for two plant parts which were aerobic (stems and leaves) and terrestrial (root and rhizomes), while the second factor included five concentrations of each aqueous extract of plant part 0, 25, 50, 75 and 100%. The results showed that there was significant effect of aqueous extract types on the studied traits; the terrestrial aqueous extract gave the highest germination percentage 64.67% and germination speed 25.37%/d, whereas the aerobic aqueous extract gave a highest mean of radicle length 2.5936 cm. Regarding of aqueous extract concentrations of Artemisia vulgaris weed, the concentration of 25% of Artemisia aqueous extract was significantly superior and achieved the highest mean of germination speed 27.25 %/day, shoot length 3.98 cm, radicle dry weight 0.0043 g and shoot dry weight 0.0239 g, while the control treatment 0% was significantly superior in the germination percentage 100% and radicle length 2.6615 cm. The interaction between two factors had significant effect on the germination percentage and germination speed only.